Influence Supervision Head School, Neighborhood Work and Motivation Work Against Teacher Performance - Mukhayanah Mukhayanah; Tri Joko Raharjo; Arief Yulianto (Universitas Negeri Semarang, 2023)
Teacher performance is very decisive achievement results Study in the learning process , however the performance of Indonesian teachers especially in Demak district is necessary get attention special because teacher performance still low Where number of certified teachers only reached 33.2% with the average score of teacher competence is 61.19. Need effort For increase teacher performance with notice internal factors as well external . Study This reveal influence supervision head school , environment work and motivation Work to teacher performance through method quantitative with approach correlational . Questionnaire study shared to 88 SMP/MTs teachers in the District Mranggen , Demak district was selected with purposive sampling. Analysis results regression showing exists influence supervision head school to teacher performance with t- count value of 10.032 1.663. Teacher performance is also influenced by the environment Work with t- count of 10.195 1.663. No Far different , results calculation regression influence motivation Work with teacher performance shows t- count value 10.238 1.663 (t- table ), so There is influence between both . Influence in a manner simultaneous based on analysis regression double showing mark F- count of 52.621 2.713, meaning all three give influence in a manner together to teacher performance . The implication enhancement teacher performance can done with notice various factor like implementation supervision by the head school , conditions environment work , and also encouragement / motivation For Work Good from motivation intrinsic nor extrinsic .